PERENCANAAN MANAJEMEN PADA STRUKTUR GEDUNG OPERASIONAL KOPERASI SIMPAN PINJAM CU PANCUR KASIH KECAMATAN PONTIANAK UTARA: PERENCANAAN MANAJEMEN PADA STRUKTUR GEDUNG OPERASIONAL KOPERASI SIMPAN PINJAM CU PANCUR KASIH KECAMATAN PONTIANAK UTARA - vadila, putri agustin (RETENSI, 2021)
In project implementation, a construction management plan is needed so that project implementation can be well planned and in accordance with the Indonesian National Standard (SNI). Therefore it is necessary to have construction management planning in the Construction of the Operational Building KSP CU Pancur Kasih, especially in building structure work, including Cost Management, Time Management, Human Resource Management (SDM), Occupational Health Safety Management (K3), and Quality Management where aspects are interconnected. The data sources used in the completion of this final project are secondary data and primary data. Based on the processed data, the final results include the Budget Plan (RAB), the Implementation Budget Plan (RAP), Time Schedule, Network Planning (NWP), Labor Needs, Mutual Check 0, Quality Checklist Table, Work Plan and Requirements, Personal protective equipment (APD) and work safety equipment (APK), which will be used as a reference or guidance and control in the implementation of development.